Temperament Dimensions and Awakening Cortisol Levels in Attention-Deficit/Hyperactivity Disorder - Carta, Alessandra; Vainieri, Isabella; Rommel, Anna-Sophie; Zuddas, Alessandro; Kuntsi, Jonna; Sotgiu, Stefano; Adamo, Nicoletta (Frontiers in Psychiatry, 2022)
Objective To investigate whether temperament dimensions, Effortful Control (EC), Surgency-Extraversion (SE), and Negative Affectivity (NA), are associated with attention-deficit/hyperactivity disorder (ADHD) and how they relate to awakening cortisol levels, as a proxy measure of peripheral arousal. Methods Parent-rated temperament and saliva samples were collected from 55 children with ADHD and 65 age-matched controls. Results Compared to controls, youths with ADHD showed lower EC, higher NA, and lower awakening cortisol levels but did not differ in SE. Similar findings emerged in dimensional analyses linking temperament traits to inattention and hyperactivity-impulsivity symptoms. The results remained unchanged when controlling for the presence of co-occurring opposition-defiance and anxiety traits, as well as medication status. Temperament dimensions were not associated with cortisol levels. Conclusions Poor temperamental emotional and cognitive self-regulation showed significant associations with ADHD but did not appear to be linked to the under-arousal typically seen in ADHD.